In situ electric field-dependent structural changes in (Ba,Ca)(Zr,Ti)O3 with varying grain size - Kuhfuß, Michel; Maier, Juliana; Hall, David A.; Xie, Bingying; Kleppe, Annette K.; Martin, Alexander; Kakimoto, Ken Ichi; Khansur, Neamul Hayet; Webber, Kyle Grant (Journal of Applied Physics, 2024)
The functional properties of piezoelectric ceramic materials, such as barium titanate, are highly dependent on grain size. Lead-free polycrystalline Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT) samples were prepared with a combination of the hydrothermal method and spark plasma sintering to achieve grain sizes from 100 nm to 10 μm by varying the maximum sintering temperature. In this range, a transition from a nearly linear dielectric to a ferroelectric response can be seen in macroscopic electromechanical measurements, demonstrating the importance of grain size on functional properties in BCZT. Furthermore, in situ electric field-dependent synchrotron x-ray diffraction measurements were performed to quantify the intrinsic and extrinsic strain contributions and their variations with grain size. At lower grain sizes, the data revealed a significant loss of extrinsic contributions in the piezoelectric behavior, limiting the response to intrinsic contribution associated with lattice strain. For BCZT, a critical grain size between approximately 0.08 and 0.18 μm is proposed, below which no piezoelectric response was observed.
CRIS-Team Scopus Importer:2024-05-17